Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas dan Profitabilitas pada PT Industri Jamu dan Farmasi Sido Muncul Tbk - Rully Movizar; Defita Ningrum (Soratekno Publisher, 2026)
PT Industri Jamu dan Farmasi Sido Muncul Tbk, a manufacturer in the herbal medicine and pharmaceutical sectors, experienced fluctuations in sales and profits during the 2022–2024 period, making it necessary to conduct a financial performance analysis to assess the company’s liquidity and profitability. The research method used was a quantitative approach employing secondary data. Data collection was conducted through documentation, while data analysis utilized liquidity and profitability ratios. Based on the research findings, the company’s liquidity ratios showed an increase during the study period. The current ratio increased from 4.05 times (2022) to 4.47 times in 2023 and 5.35 times in 2024, while the quick ratio continued to rise from 1.71 times to 1.80 times in 2023 and reached 2.08 times in 2024. Profitability ratios fluctuated, with the net profit margin declining from 28.6% in 2022 to 26.7% in 2023, but rebounding to 29.9% in 2024. Return on assets stood at 27.1% (2022), 24.4% (2023), and peaked at 29.7% in 2024, while return on equity was 31.5%, 28.1%, and 33.6%. These results indicate that the company’s financial performance is in good condition, with very strong liquidity and a return on equity that increased again in 2024.